2002
DOI: 10.1116/1.1430250
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis and optimization considerations for a Knudsen compressor in transitional flow

Abstract: The Knudsen compressor can be applied as either a vacuum pump or compressor for gases. Earlier investigations have indicated that there are several interesting potential applications of the Knudsen compressor because it has no moving parts and requires no lubricants or supplementary working fluids. However, its energy efficiency tends to be low, so that careful optimization is necessary. An important aspect of the optimization is an understanding of the Knudsen compressor’s operating characteristics in the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 16 publications
2
50
0
1
Order By: Relevance
“…In equilibrium, the pressure ratio is given by p 2 /p 1 = √ T 2 /T 1 , where p 2 and T 2 are the pressure and temperature in the warmer chamber and p 1 and T 1 are the pressure and temperature in the colder chamber. Muntz et al (2002) showed that at…”
Section: Methodsmentioning
confidence: 99%
“…In equilibrium, the pressure ratio is given by p 2 /p 1 = √ T 2 /T 1 , where p 2 and T 2 are the pressure and temperature in the warmer chamber and p 1 and T 1 are the pressure and temperature in the colder chamber. Muntz et al (2002) showed that at…”
Section: Methodsmentioning
confidence: 99%
“…In the limits relevant to this study where Kn << 1 and the transpiration-induced pressure rise is small compared to the inlet pressure, the transpiration-induced volumetric flow rate ( ), Eq. 4 in (4) reduces to the Eq. (1) below, where is the mass flow rate, P the pressure, ρ the density, c the sound speed, A the membrane area, γ the gas specific heat ratio, L the membrane thickness, T the temperature, Q T (Kn) a flow coefficient (for Kn << 1, Q T ≈ 0.64 Kn) and the subscripts 1 and 2 refer conditions at the low-temperature inlet and high-temperature outlet of the transpiration device.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work by Muntz and others on quantifying efficiency resulted in the development of parameters, which, when optimized, improved pump performance [14]. It was determined that minimizing the energy required per molecule of upflow would reduce the total power consumed, while minimizing the volume per molecule of upflow would reduce the total volume of the pump.…”
Section: Knudsen Pump Ideal Efficiency Though An Aperturementioning
confidence: 99%
“…al. have shown that the power consumption of a series of cascaded pumps is greatly reduced by allowing operation during the transition stage, where both the pressure and the thermal transpiration flow are significant [14]. The efficiency of the pump is reduced as the differential pressure increases due to thermal transpiration moving molecules against the pressure gradient.…”
mentioning
confidence: 99%
See 1 more Smart Citation